A Simplified Silty Sand Model - Nopanom Kaewhanam; Krit Chaimoon (Applied Sciences, 2023)
A unified critical state model has been developed for both clean sand and silty sand using the modified Cam-clay model (MCC). The main feature of the proposed model is a new critical state line equation in the e-ln(p) plane that is capable of handling both straight and curved test results. With this feature, the error in calculating plastic volumetric strain is, in theory, eliminated. Another crucial feature of the model is the transformed stress tensor based on the SMP (spatially mobilized plane) criterion, which takes into account the proper shear yield and failure of soil under three-dimensional stresses. Additionally, the proposed model applies the intergranular void ratio with the fines influence factor for silty sand. Only eight soil parameters are required for clean sand, and a total number of twelve soil parameters are needed for silty sand. This model not only enhances the predictive accuracy for granular soils but also broadens the applicability of the model to encompass silty sand in both drained and undrained analyses.